2017
DOI: 10.18502/kls.v3i5.981
|View full text |Cite
|
Sign up to set email alerts
|

A Glimpse into the Biosynthesis of Terpenoids

Abstract: Terpenoids represent the largest class of natural products with a diverse array of structures and functions. Many terpenoids have reported therapeutic properties such as antimicrobial, anti-inflammatory, immunomodulatory and chemotherapeutic properties making them of great interest in the medical field. Also, they are widely used in the flavors and fragrances industries, in addition to being a source of biofuels. Terpenoids suffer from low natural yields and complicated chemical synthesis, hence the need for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…These are (1) geranyl pyrophosphate (GPP; C 10 ) produced by geranyl pyrophosphate synthase (GPPS) for the synthesis of monoterpenoids, (2) farnesyl pyrophosphate (FPP; C 15 ) produced by farnesyl pyrophosphate synthase (FPPS) for the construction of sesquiterpenoids and triterpenoids, and (3) geranylgeranyl pyrophosphate (GGPP; C 20 ) synthesized by geranylgeranyl pyrophosphate synthase (GGPPS) for the production of diterpenoids and tetraterpenoids. Finally, these starting precursors are cyclized and/or rearranged by terpene synthase enzymes to yield the different terpenoids (Withers and Keasling, 2007; Muntendam et al., 2009; Abdallah and Quax, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are (1) geranyl pyrophosphate (GPP; C 10 ) produced by geranyl pyrophosphate synthase (GPPS) for the synthesis of monoterpenoids, (2) farnesyl pyrophosphate (FPP; C 15 ) produced by farnesyl pyrophosphate synthase (FPPS) for the construction of sesquiterpenoids and triterpenoids, and (3) geranylgeranyl pyrophosphate (GGPP; C 20 ) synthesized by geranylgeranyl pyrophosphate synthase (GGPPS) for the production of diterpenoids and tetraterpenoids. Finally, these starting precursors are cyclized and/or rearranged by terpene synthase enzymes to yield the different terpenoids (Withers and Keasling, 2007; Muntendam et al., 2009; Abdallah and Quax, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The GGPP precursor can be synthesized via the MVA and/or the MEP pathway as previously explained. Taxadiene is converted to the final product, paclitaxel, through approximately 19 enzymatic steps involving hydroxylation and other oxygenation reactions of the taxadiene skeleton (Hezari and Croteau, 1997; Julsing et al., 2006; Abdallah and Quax, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our observation we propose that the genus Planococcus produces terpene containing BS through non-mevalonate pathway. It has been suggested that the terpene synthases are mainly responsible in contributing the diversity as well as complexity of the metabolites produced by the microbial system (Abdallah and Quax, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Terpene synthases perform complex chemical rearrangements leading to the production of terpenoids. The structural diversity of terpenoids is centered on the positioning of their substrate in the active site of the terpene synthase so it can undergo the required cyclizations and/or modifications to give the desired structure of the final product (1,2). Terpene synthases generally, and sesquiterpene synthases precisely, perform intricate catalytic mechanisms to produce their final product.…”
mentioning
confidence: 99%